2018
DOI: 10.1039/c7ee01630a
|View full text |Cite
|
Sign up to set email alerts
|

Flexible/shape-versatile, bipolar all-solid-state lithium-ion batteries prepared by multistage printing

Abstract: The flexible/shape-versatile bipolar all-solid-state LIBs, which fabricated via solvent-drying-free, UV-curing-assisted multistage printing, are presented as an unprecedented material/process strategy to address longstanding challenges associated with inorganic-electrolyte-based bipolar LIBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(88 citation statements)
references
References 37 publications
0
82
0
Order By: Relevance
“…[45][46][47] Yet, the electrochemical alloying reaction between Al and Li can easily occur at < 0.5 V vs. Li/Li + : Al has been only used in the BPs of SSLBs assembled with high-potential NEs, e. g., Li 4 Ti 5 O 12 (~1.5 V vs. Li/ Li + ) and 2,6-naphthalene dicarboxylate dilithium (~0.8 V vs. Li/ Li + ). [163,164] Although Ni is less suitable for high-potential PEs compared to Al, it is known to exhibit acceptable chemical stability in certain electrolytes (e. g., LiAlCl 4 in SO 2 ). [46,165] Ni has been used as BPs for the Li NE and TiS 2 PE, [46] and more recently, Nam et al demonstrated the chemical stability of Ni with a Li 3 PS 4 SE and constructed a free-standing, stackable, bipolar SSLB using a Ni-coated non-woven scaffold BP.…”
Section: Bipolar Platesmentioning
confidence: 99%
See 3 more Smart Citations
“…[45][46][47] Yet, the electrochemical alloying reaction between Al and Li can easily occur at < 0.5 V vs. Li/Li + : Al has been only used in the BPs of SSLBs assembled with high-potential NEs, e. g., Li 4 Ti 5 O 12 (~1.5 V vs. Li/ Li + ) and 2,6-naphthalene dicarboxylate dilithium (~0.8 V vs. Li/ Li + ). [163,164] Although Ni is less suitable for high-potential PEs compared to Al, it is known to exhibit acceptable chemical stability in certain electrolytes (e. g., LiAlCl 4 in SO 2 ). [46,165] Ni has been used as BPs for the Li NE and TiS 2 PE, [46] and more recently, Nam et al demonstrated the chemical stability of Ni with a Li 3 PS 4 SE and constructed a free-standing, stackable, bipolar SSLB using a Ni-coated non-woven scaffold BP.…”
Section: Bipolar Platesmentioning
confidence: 99%
“…Although the non-fluidic properties of SEs enable a bipolar design by preventing the flow of ions between adjacent cells, the stacking of multiple cells within a single package has been found to be very challenging, and only a few reports on bipolar SSLBs, mostly proof-of-concept studies, have been published thus far. [37,38,149,163,166,170,[173][174][175][176][177][178] The stacking strategies for bipolar SSLBs reported in the literature may be broadly classified into (i) the lamination of free-standing SE sheets and (ii) the printing of SE slurries. The former involves the sequential lamination of free-standing SE sheets and electrode-coated BPs, both of which have sufficient mechanical stability.…”
Section: Fabrication and Electrochemical Properties Of Bipolar-type Smentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11][12][13] With increasing interest in portable and flexible electronics,c onsiderable efforts have been investedi nt he fabrication of solid-state microbatteries that can be implemented in wearable or implantable devices. [16][17][18][19][20] In general, large-scale energy storage devices,f or example, for EV applications,r equire high-voltage and high-energy battery modules that possess numerous unit cells connected in series. [16][17][18][19][20] In general, large-scale energy storage devices,f or example, for EV applications,r equire high-voltage and high-energy battery modules that possess numerous unit cells connected in series.…”
Section: Introductionmentioning
confidence: 99%